The predictive value of laboratory factors in evaluating the necessity of surgical treatment in Crohn’s disease (Annals of Medical Research, 2021)
Aim: The primary treatment of Crohn’s disease (CD) is medical but approximately 70% of all patients with CD undergo surgical intervention throughout their lives. We aimed to determine which parameters can guide decision making before surgical treatment and to determine the effectiveness of the Glasgow prognostic index (GPI) and prognostic nutritional index (PNI) in predicting the necessity of surgery.Material and Methods: Patients who underwent surgery or medical treatment for CD were matched for age and sex. Group 1: operated patients; Group 2: received medical treatment. Hemogram and biochemistry test results were recorded. Platelet to neutrophil ratio (PNR), Neutrophil to lymphocyte ratio (NLR), and Lymphocyte to monocyte ratio (LMR) were calculated. Patients who had both a serum elevation of CRP (>1.0 mg/dL) and hypoalbuminemia (3.5 g/dL) were allocated a GPI of 2. Patients with only one of the abnormal values were allocated a GPI of 1, and patients who had neither were allocated a GPI 0. Parameters compared statistically between groups. The value p0.05 was accepted significant.Results: Of the 104 patients 51 were in Group 1 and 53 were in Group 2. The number of patients with a GPI value of 3 was significantly higher in Group 1 than in Group 2 (p 0.05), as were NLR, protein, albumin, neutrophil, platelet, and CRP levels (p 0.05). The multivariate analysis revealed that albumin and GPI values were independent variables in predicting the likelihood of receiving an operation in CD. Conclusion: In conclusion, evaluating the necessity of surgical treatment during follow-up for CD, neutrophil, NLR, CRP, albumin, platelet, PNI, and GPI, can be used. If the GPI value is 2 in a patient with CD under follow-up whose albumin levels are low, then surgical treatment should be considered.
Keywords: Crohn’s disease; blood test; surgery; medical treatment